Cover it up! Visual euphemisation strategies for transforming non-religious songs into Islamic songs in music videos - Ikke Dewi Pratama; SF Luthfie Arguby Purnomo; Arina Rohmatika; Nestiani Hutami (Studies in English Language and Education, 2024)
In Indonesia, covering songs with an Islamic theme has become a trend that is gaining more and more popularity. Several content creators have recently covered non-religious songs by changing the lyrics to ones loaded with Islamic teachings. As the cover songs are uploaded on YouTube, inevitably, there are versions of cover music videos in which some elements of the original music videos are euphemized to fulfill the purpose of religious wisdom. This study not only attempts to examine the visual elements euphemized in the cover music videos but also the visual euphemization strategies employed by the content creators. The data were gathered from YouTube in the form of twelve original music videos and their covers. Furthermore, a localization approach, the theory of euphemism, and para-adaptation were employed to analyze the data. The results of the study revealed that four visual elements were euphemized in these cover songs: the properties, costumes, locations, and interactions among the singers or models. Delving deeper into this, the researchers proposed four visual euphemization strategies, including peripheralization (euphemization of the properties), vestimentarization (euphemization of the costumes), locationalization (euphemization of the locations), and interactionalization (euphemization of the interactions). These findings interestingly highlight that there is a common visual euphemization strategy used by content creators when covering music videos of non-religious songs into Islamic songs. Thus, the findings suggest that content creators may apply the four proposed strategies to create acceptable cover music videos to spread Islamic teachings.